1980
DOI: 10.5962/bhl.title.130165
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the instream flow requirements for selected fishes in the wild & scenic portion of the Missouri River /

Abstract: Spawning Conditions of sauger sampled in the Fort Benton through Judith Landing study sections of the middle Missouri River during spring and early summer 1979 2 Spawning conditions of shovelnose sturgeon sampled in the Loma Ferry and Coal Banks Landing study sections of the middle Missouri River during late spring and summer 1979 3 Number of egg samples taken and number of eggs collected (in parentheses) in four study sections on the middle Missouri River during 1979 4 Taxonomic composition of fish larvae sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 7 publications
3
28
1
Order By: Relevance
“…Low niche overlap values confirmed that juvenile pallid sturgeon and shovelnose sturgeon used different food resources. These results are similar to those reported for adult pallid sturgeon (Coker 1930;Cross 1967;Carlson et al 1985) and for shovelnose sturgeon (Barnickol and Starrett 1951;Hoopes 1960;Held 1969;Helms 1974;Modde and Schmulbach 1977;Gardner and Berg 1980;Carlson et al 1985;Megargle 1996;Shuman 2003). The results of this study support neither our prediction nor the speculation of Bramblett and White (2001) that small pallid sturgeon consume more aquatic insects than fish.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Low niche overlap values confirmed that juvenile pallid sturgeon and shovelnose sturgeon used different food resources. These results are similar to those reported for adult pallid sturgeon (Coker 1930;Cross 1967;Carlson et al 1985) and for shovelnose sturgeon (Barnickol and Starrett 1951;Hoopes 1960;Held 1969;Helms 1974;Modde and Schmulbach 1977;Gardner and Berg 1980;Carlson et al 1985;Megargle 1996;Shuman 2003). The results of this study support neither our prediction nor the speculation of Bramblett and White (2001) that small pallid sturgeon consume more aquatic insects than fish.…”
Section: Discussionsupporting
confidence: 89%
“…Pallid sturgeon Scaphirhynchus albus were listed as endangered in 1990 (Dryer and Sandvol 1993) and the abundance of shovelnose sturgeon S. platorynchus has declined over the past 100 years (Keenlyne 1997). Aquatic insects are the primary prey of shovelnose sturgeon (Barnickol and Starrett 1951;Hoopes 1960;Held 1969;Helms 1974;Modde and Schmulbach 1977;Gardner and Berg 1980;Megargle 1996;Shuman 2003), but little information exists on the food habits of pallid sturgeon. Coker (1930) and Cross (1967) both noted that fish were in the diets of adult pallid sturgeon.…”
mentioning
confidence: 99%
“…The ''wild and scenic'' designation prohibits construction of any dams on protected waters and imposes protective regulations on any new development in areas surrounding the protected area (U.S. Congress 1975b). Water diversions and pumping of water from the protected area for agricultural purposes are still permitted, as are row crop farming and cattle grazing within the immediate watershed (Gardner and Berg 1980). Limited storage of upstream dams, lack of channelization, and unregulated tributaries make the Missouri River above Fort Peck Reservoir the least hydrologically altered portion of the Missouri River (Scott et al 1997;Pegg et al 2003).…”
Section: Study Areamentioning
confidence: 99%
“…Impoundment and subsequent flow management isolate saugers from important spawning and rearing habitats, reduce turbidity and temperature, and alter the timing and magnitude of the hydrograph from the natural regime in which saugers evolved (Hesse 1994;McMahon and Gardner 2001). Channelization reduces off-channel rearing habitats (Gardner and Berg 1980;Hesse 1994). Unrestricted access to widely separated and diverse habitat types throughout the year is critical to riverine fishes in general (Schlosser 1991;Fausch et al 2002).…”
mentioning
confidence: 99%